2010
DOI: 10.1021/jp100423b
|View full text |Cite
|
Sign up to set email alerts
|

Nature and Strength of M−S Bonds (M = Au, Ag, and Cu) in Binary Alloy Gold Clusters

Abstract: The interactions of pure (Au(k), Ag(k), and Cu(k); k = 1-3) and binary alloy (Au(n)Ag(m) and Au(n)Cu(m); m + n = k Cu > Ag. In binary alloy clusters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
113
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(129 citation statements)
references
References 81 publications
16
113
0
Order By: Relevance
“…The Ag-O bond lengths range from 2.2363(3) to 2.470(2) Å ( Table 2) and are in accordance with reported values [19]. Similarly, the Ag-S distance of 2.5679 Å (Ag1-S3 4 ) and 2.5841 (9) Å are also in agreement with the previously reported Ag-S bond distance [20,21]. A closure look at 1 reveals a novel coordination mode of the tdga 2- (Fig.…”
Section: Resultssupporting
confidence: 91%
“…The Ag-O bond lengths range from 2.2363(3) to 2.470(2) Å ( Table 2) and are in accordance with reported values [19]. Similarly, the Ag-S distance of 2.5679 Å (Ag1-S3 4 ) and 2.5841 (9) Å are also in agreement with the previously reported Ag-S bond distance [20,21]. A closure look at 1 reveals a novel coordination mode of the tdga 2- (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Thermochemical data for the solvated species were obtained only on B3LYP level of theory as its performance to predict the binding energies of Cu complexes have been shown to be superior to the MP2 method by several authors (Ignaczak and Gomes, 1996;Luna et al, 2000;Pakiari and Jamshidi, 2010). Indeed, some authors pointed out that the B3LYP theory performs nearly as well or even better on Cu complexes than the computationally much more demanding CCSD(T) level of theory (Luna et al, 2000;Pakiari and Jamshidi, 2010), which almost fully accounts for electron correlation energies. To test the robustness of our results, we conducted CCSD(T)/6-311++G(d,p) level single point energy calculations on the B3LYP/6-311++G(d,p) optimized geometries within the PCM.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…23 Poly(ethylene glycol) derivatives are often used as stabilizers for gold nanoparticles because of their biocompatibility, stealth action, their potential multiple chemical functionality (upon modification) and their ease of grafting due to the high affinity of thiol or amino groups to the gold surface. [24][25][26][27][28] We have recently demonstrated that PEG chains can also be used as a thermoresponsive surface coating at sufficiently high ionic strengths to trigger the clustering of gold particles. 23 In this paper we show how this process can be fine-tuned by adjusting two easily controlled environmental parameters (temperature and ion concentration) that affect the clustering process (kinetics and NPC structure) through modulating colloidal interactions (see Scheme 1).…”
Section: Introductionmentioning
confidence: 99%